2018
DOI: 10.20944/preprints201811.0563.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MiR-125b-2 Knockout in Testis Are Associated with Targeting to PAP Gene, Mitochondrial Copy Number and Impaired Sperm Quality

Abstract: microRNAs can cause male infertility by impacting sperm quality and impaired spermatogenesis. Since the miR-125 family plays an important role in regulating embryo development, but the function of miR-125b-2 in male reproduction remains unknown. In this study, we prepared a model of miR-125b knockout (KO) mice. Among the KO mice, the progeny test showed that litter sizes decreased significantly and the rate of non-parous females increased significantly (p<0.05). At the same time, the testosterone concen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The GC-2 spermatocyte cells were transfected for studying the function of the miRNA-450b-3p in these cells after exposure to the SiNPs. The present results showed that SiNPs downregulated the expression of (31) demonstrated that miR-125b-2 regulated testosterone secretions by targeting Papolb, and increased the DNA copy number of sperm mitochondria to in uence the semen quality. In male mice, miR-34b/c and − 449a/b/c led to sperm aggregation and agglutination, luminal obstruction, and sperm granulomas in male mice (32).…”
Section: Discussionsupporting
confidence: 51%
“…The GC-2 spermatocyte cells were transfected for studying the function of the miRNA-450b-3p in these cells after exposure to the SiNPs. The present results showed that SiNPs downregulated the expression of (31) demonstrated that miR-125b-2 regulated testosterone secretions by targeting Papolb, and increased the DNA copy number of sperm mitochondria to in uence the semen quality. In male mice, miR-34b/c and − 449a/b/c led to sperm aggregation and agglutination, luminal obstruction, and sperm granulomas in male mice (32).…”
Section: Discussionsupporting
confidence: 51%
“…13 Evidence has shown that some miRNAs are abundantly expressed in various type of male germ cells. 14 Abu-Halima et al found that the level of miR-200a was notably upregulated in patients with different spermatogenic impairments. 15 However, the mechanism by which miR-200a regulated spermatogenic impairments remains unclear.…”
Section: Introductionmentioning
confidence: 99%